THE IMPLEMENTATION OF ISOMETRIC HANDGRIP EXERCISES TO REDUCE BLOOD PRESSURE IN PATIENTS WITH HYPERTENSION: CASE REPORT - Lu'lu Nurhaliza; Agis Taufik (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Introduction: As we age, decreased physiological function coupled with an unhealthy lifestyle can increase the risk of hypertension. Hypertension is a non-communicable disease characterized by systolic blood pressure ≥140 mmHg and diastolic pressure ≥90 mmHg. Lifestyle modification, such as physical activity, is a non-pharmacological treatment of hypertension. One static physical activity that can be done to control blood pressure is isometric handgrip exercise. Purpose: This case study aims to determine the results of Isometric Handgrip Exercise therapy on lowering blood pressure in patients with hypertension. Methods: Case study research with isometric handgrip exercise intervention as Evidence-Based Nursing. The intervention was carried out once per day for five days, with a contraction duration of 45 seconds and relaxation of 15 seconds. Each hand has two contractions. Discussion: The case study results showed a decrease in blood pressure in patients with hypertension after the intervention for 5 days. The first respondent's blood pressure decreased from 144/94 mmHg to 120/87 mmHg. The second respondent's blood pressure, originally 151/98 mmHg, decreased to 132/86 mmHg. Conclusion: Isometric handgrip exercise intervention is proven to be successful in reducing blood pressure in hypertensive patients.